Propagation of coffee conilon “Vitória” in conventional and alternative substrates - da Silva Berilli, Sávio; Amaro de Salles, Rodrigo; Amaro de Sales, Ramon; Alvino Falcão Zooca, Alan; Rodrigues Ribeiro, Helder; Candido Gabriel Berilli, Ana Paula; Souza Costa, Taiara; Pacheco Mendes, Tiago; Zancanella Quartezani, Waylson (Coffee Science - ISSN 1984-3909, 2020)
The sustainable production of inputs or products, either agricultural or industrial, has become an international concern in the last years. Thus, one of the biggest challenges today is to combine production with sustainability. An alternative that has been gaining strength is the use of industrial waste in agriculture. Therefore, the objective of this study was to evaluate the development, physiology and quality of seedlings of C. canephora from the thirteen genotypes found in the variety Vitória Incaper 8142, in conventional substrate in comparison to a substrate based on tannery sludge. A 2 x 13 factorial arrangement was used in which the first factor was the two substrates (conventional substrate and substrate with tannery sludge), and the second factor was the 13 Vitória - Incaper 8142 Conilon coffee genotypes, arranged in a randomized block design with four repetitions. No significant interaction was observed between the factors evaluated, genotypes and substrates. Despite the fact that plants grown on substrate based on tannery sludge show lower averages in some characteristics, they were not different in terms of seedling quality index, so the substrate based on tannery sludge has strong potential for use. This substrate also promoted a greater production of defense metabolites in plants. As for the response pattern between the genotypes of the Vitória - Incaper 8142 variety, a high unevenness was observed in the initial development, both for their phenological and physiological characteristics, which is a reflect of the genetic variability existing between the genotypes. Key words: Seedling production; Coffe canephora; physiology; sustenaibility.